IDDF2018-ABS-0056 Long term outcomes of initial infliximab therapy for inflammatory pouch pathology: a multi-centre retrospective study. (June 2018) - Segal, Jonathan; Penez, Lawrence; Elkady, Soad; Worley, Guy; McLaughlin, Simon; Mullish, Benjamin; Quraishi, Mohammed; Ding, Nik; Glyn, Tamara; Kandiah, Kesavan; Samaan, Mark; Irving, Peter; et al.
Abstract : Background: Restorative proctocolectomy is considered the procedure of choice in patients with UC refractory to medical therapy. Inflammation of the pouch is a common complication and in some cases fails to respond to antibiotics, the mainstay of treatment. In such cases, corticosteroid, immunomodulatory or biologic treatments are an option. However, our understanding of the effectiveness of IFX for both chronic pouchitis and Crohn's-like inflammation are based on small studies. Methods: This was an observational, retrospective, multi-centre study to assess the effectiveness IFX for inflammatory disorders related to the pouch. The primary outcome was the development IFX failure defined by primary non-response or secondary loss of response to IFX. Results: 38 patients were included. 20/38 (53%) who were initiated on IFX for inflammatory disorders of the pouch had IFX failure, 4/38 (11%) had primary non-response, and 16/38 (42%) had secondary loss of response with a median follow-up of 265 days (range 82–2119). Of those that had IFX failure 10/20 (50%) avoided an ileostomy by switching to an alternative biologic. In total, 28/38 (74%) avoided an ileostomy, of these, 17/38 (45%) continued on their IFX after a median follow-up of 311 days (42–3968), 5/38 (13%) were changed to Adalimumab after a median follow-up of 498 days (1–1544), 4/38 (11%) were changed to Vedolizumab after a median follow-up of 569 (251–1138), 1 achieved histological remission and stopped all treatments at 251 days and 1 was maintained on methotrexate and multiple antibiotics after 3968 days. Conclusions: After initial IFX therapy over half will fail first line IFX, of those that fail half can avoid an ileostomy by switching to an alternative biologic. Patients should be counselled about a high incidence of failure and alternatives should be considered.